Preferential Weld corrosion of carbon steel as Effect of Caustic in amine-CO2 contained solutions - Yuli Panca, Asmara; Muhammad Izzat Nor, Ma'arof; A.G.E, Sutjipto (INTI International University, 2020)
Technology to remove CO2 gas from power plant emission are urgently required as wide impacts on environmental degradation. To date the primary compounds for CO2 solvents are dominated by amines-based solvent such as monoethanolamine (MEA), diethanolamine (DEA), and methyldiethanolamine (MDEA). To improve adsorption system and prevent corrosion effect on metallic structure, Mitsubishi Heavy Industries (MHI) had developed solvent called KS-1. However, the use of KS-1 had caused several leakages on welding area in flue gas-CO2 separation unit. It was reported that the failures occurred on different types of corrosion; carbonic acid and caustic corrosion. To investigate the corrosion rate on the weld area, it was conducted researches to determine the mechanism of the corrosion particularly on the roles of caustic and pH in relation with KS-1. In this research, the corrosion rate of carbon steel in KS-1 solvent solutions combined with saturated CO2 gas and caustic solutions were studied. The experiments were carried out in static conditions and the linear polarization resistance (LPR) technique were used to measure the corrosion rate (as per ASTM G 5-94). It was found that the corrosion rate of base metal in the KS-1 mixed with caustic solutions did not show significant effects. At the base metal, the corrosion rate tends to be unvarying at adding caustic solution from 50 ppm to 500 ppm which was 0.05 mm/y. In contrast with on weld metal area, the corrosion rates were significantly high. The highest corrosion rate was at 500 ppm caustic solution which was 0.5 mm/y. The differences in microstructure and reaction activation of the samples may relate to the increase of corrosion process.